An Integrated Practical Evidence-Based Medicine Curriculum: Two Small-Group Sessions to Teach PICO Question Formation and Searching Strategies - Rachel Boykan; Maribeth Chitkara; Colleen Kenefick; Catherine Messina (Association of American Medical Colleges, 2013)
Abstract Introduction The need to teach evidence-based medicine (EBM) goes beyond meeting the requirements of residency. For residents and all practicing physicians, there must be a process to ensure that doctors know the latest and best information to apply to the care of their patients. Typically, in the majority of pediatric training programs, EBM is taught in the context of a journal club, which may not develop the skills needed to integrate EBM into one's own clinical practice. These two small-group sessions focus on the basics of EBM: asking the question and searching for the answer. Methods In two 1.5-hour sessions, learners were introduced to basic EBM principles such as how to pose an answerable question in patient/population/problem, intervention/indicator, comparison, outcome (PICO) format, and how to efficiently utilize evidence-based resources. Each session begins with a brief (10 minute) introduction. Utilizing the principles of active learning, the group works through one example together then breaks into smaller groups for further practice. The completion and review of homework given after each session helps learners to apply and reinforce basic principles and skills learned during the group sessions. Results In an initial pilot evaluation of these two sessions, four interns revealed improved knowledge and efficiency in using EBM. Subsequent evaluations of 9-10 interns per year completing the entire longitudinal curriculum have reinforced the findings of the pilot. These data have been presented at many regional and national conferences, including the Association of Pediatric Program Directors (APPD) meeting in 2011, the Pediatric Educational Excellence Across the Continuum (PEEAC) conference in 2011, the Northeastern Group On Educational Affairs (NEGEA) meeting in 2012, at the Pediatric Academic Society Meeting in 2012, and at Women in Medicine Day, Stony Brook University Medical Center in 2012. Discussion While the curriculum was designed for and has been studied on pediatric residents, it could easily be adapted for use by a broader audience including residents of any specialty, and medical students in their last 2 years of medical school.